Computational cost of an exergy-based fault detection scheme implemented in a commercial process simulator. Issue 14 (2019) - Marais, Henri; Schoor, George van; Uren, Kennith R.
Abstract: Energy-based fault detection and isolation (FDI) schemes show promise in terms of applicability to petrochemical industries and the broader process industries. Model-based FDI schemes offer pronounced advantages over more easily implemented data-driven FDI techniques. However, the implementation of model-based FDI schemes require the development of analytic models, and as such, widespread adoption is lacking. Although process simulators derive analytic models internally, comprehensive exergy-based parameters are not calculated automatically. In this work Aspen Hysys is extended by means of user variables to allow the automatic calculation of physical and chemical exergy for each process stream. Initial results indicate that additional computational overhead of approximately 20% is incurred and that the calculation technique scales well with model size. This calculation method allows the development of a truly hybrid model- and data-based approach to FDI within the process industries.